A Driver Health Monitoring-based Accident Prevention System for Commercial Vehicles in India - Mali, Abhijit S; Ghugare, Sukhada (International Journal of Engineering and Management Research, 2024)
In the growing nation, road transportation is crucial. Accident rates will rise in tandem with an increase in road traffic. There are several categories in which accidents might arise. Among these reasons, one significant cause—the accident resulting from a heart attack—is chosen here. The majority of the time, it is seen that drivers who experience heart attacks abruptly lose control of their vehicles, which leads to accidents. The suggested system aims to address this problem by identifying heart attack symptoms early and automatically slowing down the vehicle. It also applies a gentle hand brake to bring the car to a stop, and it uses GSM services to send a GPS-coordinated message to the relevant department, such as the health department. The goal of the suggested approach is to raise the survival rate.